Pengaruh Pemberian Beberapa Jenis Pupuk Kandang Dan Frekuensi Penyiraman PGPR terhadap Pertumbuhan dan Hasil Sorgum (Sorgum Bicolor L.) Lokal - Stefania Kolo (Savana Cendana, 2021)
An experiment was carried out using the type of manure and frequency of watering PGPR to increase the productivity and yield of sorghum plants (Sorghum bicolor L.). The research aims to determine the impact of growth and production of sorghum (Sorghum bicolor L.). By using the type of manure and frequency of PGPR irrigation. This research was conducted in the experimental garden of the Faculty of Agriculture, University of Timor, in January-April 2019, the design used was a factorial randomized 3x3x3 randomized block design with 3 replications. The first factor is the type of Manure (K) namely: Without Cow Manure (K0), Cow Manure (K1), Goat Manure (K2). The second factor is the frequency of watering PGPR (F) namely: Without watering PGPR (F0), twice watering (F1), three times watering (F2). Variance results (Anova) showed that without the administration of types of manure and without the frequency of watering PGPR interacted positively (P <0.05) in influencing the value of the harvest index. The main effect of single factor type of goat manure on average shows the best results that can be expressed in the form (lowest soil temperature, moisture content 42 and 180 HST highest, plant height 15, 45 and 75 HST highest, highest number of leaves 45 HST, stem diameter 45 of the largest HST, the heaviest dry weight per plant, the heaviest dry weight of 1000 seeds, the heaviest seed dry weight population, the lowest disease severity and the heaviest stover dry weight while the single factor of PGPR watering frequency did not show any significant difference between treatment levels.